Estudo do efeito da antibioticoterapia profilática pré-operatória com amoxicilina em cirurgias de terceiros molares - Bezerra, Tácio Pinheiro (2009)
Post-operative inflammatory-infectious changes after the removal of third molars are often associated with bacterial contamination of the surgical site in the trans-operative period. Thus, this study aims to conduct a prospective, double-blind, placebo-controlled randomized clinical trial with split-mouth metodology, to evaluate the effect of preoperative prophylactic administration of amoxicillin in the control of infectious-inflammatory events associated with surgery for the removal of third molars. After application of inclusion and exclusion criteria for patients seeking odontological attention in the discipline of Bucco-Dental Surgery and Clinic Stomatology in the Course of Dentistry in the Universidade Federal do Ceará during the period from January to November of 2008, a sample of 34 patients was obtained. Each patient was his own control, since the standardization of dental inclusion allowed the comparison between the sides of the mouth of a patient, and received two separate surgical procedures randomly chosen. The experimental side was the surgical procedure that used an initial prophylactic dose of 1 gram of amoxicillin one hour before the procedure to remove an upper and lower third molar from one side. The control side was the other in witch the patient received placebo capsules in the same way of the experimental side. The surgical procedure was standardized and performed by the same surgical team. The parameters evaluated were pain, swelling, maximum mouth opening, hyperthermia and oral findings in revaluations after 3, 7 and 14 days of the surgery. To the analysis of continuous variables was used the parametric T-student test for independent samples and the chi-square test for the analysis of categorical variables. In comparisons, bilateral tests were used where the level of significance adopted in this study was α = 0.05. The p-value was considered statistically significant when equal or less than 0.05. As regards the occurrence of general infectious-inflammatory events between the studied groups, there were no statistically significant differences in the revaluations. There was a significant reduction of painful symptoms assessed on the seventh postoperative day in the experimental group compared with the control, significant pattern was also observed on the third postoperative day on a greater magnitude of mouth opening in the experimental group compared to control. Under the conditions of this study it was concluded that the use of preoperative prophylactic antibiotic therapy was not effective in reducing the occurrence of inflammatory-infectious events (edema, hyperthermia and oral findings) in the postoperative periods evaluated, except for the painful symptoms and maximal mouth opening respectively on the seventh and third postoperative day, and that the systematic use of antibiotic medication can expose the patient to an unwanted risk of bacterial resistance adverse effects, related to the medication, without giving a clear explanation for benefits related to its use.